New insights of phenolic compounds from optimized fruit extract of Ficus auriculata - M. Shahinuzzaman (Nature Portfolio, 2021)
Abstract In this study, the extraction conditions extracted maximize amounts of phenolic and bioactive compounds from the fruit extract of Ficus auriculata by using optimized response surface methodology. The antioxidant capacity was evaluated through the assay of radical scavenging ability on DPPH and ABTS as well as reducing power assays on total phenolic content (TPC). For the extraction purpose, the ultrasonic assisted extraction technique was employed. A second-order polynomial model satisfactorily fitted to the experimental findings concerning antioxidant activity (R2 = 0.968, P < 0.0001) and total phenolic content (R2 = 0.961, P < 0.0001), indicating a significant correlation between the experimental and expected value. The highest DPPH radical scavenging activity was achieved 85.20 ± 0.96% at the optimum extraction parameters of 52.5% ethanol (v/v), 40.0 °C temperature, and 22 min extraction time. Alternatively, the highest yield of total phenolic content was found 31.65 ± 0.94 mg GAE/g DF at the optimum extraction conditions. From the LC–ESI–MS profiling of the optimized extract, 18 bioactive compounds were tentatively identified, which may regulate the antioxidant activity of fruits of F. auriculata.